The role of leadership in collective creativity and innovation: Examining academic research and development environments - Huang, Zijian; Sindakis, Stavros; Aggarwal, Sakshi; Thomas, Ludivine (Frontiers in Psychology, 2022)
Introduction Leadership is pragmatically linked to innovation adoption and implementation at a team level, as managers oversee the strategic decisions and policymaking, control resources, and moderate the scanning and searching of the environment. The paper attempts to provide new concepts and examines theoretical and practical implications to better understand how the leadership role is executed in an R&D environment to foster team creativity and innovation. Methods A quantitative analysis was plausible over qualitative research mainly because the survey was conducted using a single technique, employing a questionnaire that was selected after checking the principal component analysis (PCA) and confirmatory factor analysis (CFA). Results The findings show that the production of ideas positively impacts leadership, leading to growth and competitive advantage for the organization. Also, the PMEG (people, means, effects, goals) framework will positively impact leadership as leaders focus on those factorsthat influence an individual’s attitudes, behaviors, and interactions between groups. Discussion The paper highlights the involvement of R&D organizations and groups in developing innovative products, services, technologies, and processes that further positively impact a team. This study is the first to highlight the role of the PMEG framework with the factors that influence an individual’s attitudes, behaviors, and interactions between groups. The study’s main contribution is to explore creativity as a potential mediator for leadership–organizational innovation.